Space Curious Questions and Answers - Becklake , Sue; Bakos, Barbara; Gomez, Ana; Graham , Ian; Reeves, Pauline; Rooney, Anne; Semple, Lucy (Essex, UK Miles Kelly Publishing Ltd, 2020)
This brilliantly bonkers book takes a sideways look at all that is wild, wonderful and downright weird about space, including the topics of astronauts, space machines and the moon. Colourful, quirky illustrations and playful text reveal the amazing answers to the most curious of questions. Find out how astronauts survive living on a space station, which space probes have travelled out of the solar system and how the moon moves oceans on Earth
The World Around Us (Outer Space)
Keywords: Space